2019
DOI: 10.1021/acsaem.9b01329
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of Cr2CO2 MXene Supported Single Metal Atom as an Efficient Bifunctional Electrocatalyst for Overall Water Splitting

Abstract: Nanostructure-supported single-atom bifunctional catalysts can reduce the usage of catalyst and improve the catalytic activity compared with unifunctional catalysts. Developing effective bifunctional electrocatalysts for water splitting is one of the central issues to the area of renewable energy. Herein, we report a single transition-metal atom anchoring on the Cr2CO2 MXene surface as bifunctional eletrocatalyst for water splitting through density functional theory calculations. Results show that Ni anchored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…MXenes, a novel new family of two‐dimension material, have been combined with other materials to catalyze OER . Experimental and theoretical studies demonstrate that MXenes are the efficient supporting materials for stabilizing single metal atoms . Particularly, Ti 3 C 2 T x , Ti 2 CO 2 , Ti 2 NO 2 , V 2 NO 2 , CrNO 2 , Cr 2 CO 2 , Mo 2 TiC 2 T x, Ti 3 C 2 O 2 , Ti 3 CNO 2 , and Mo 2 CO 2 , are reported as effective supporting materials for monoatomic Pd, Ti, Cu, Mo, Pt, Ni catalysts for CO 2 conversion, CO oxidation, ORR, NRR and HER.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MXenes, a novel new family of two‐dimension material, have been combined with other materials to catalyze OER . Experimental and theoretical studies demonstrate that MXenes are the efficient supporting materials for stabilizing single metal atoms . Particularly, Ti 3 C 2 T x , Ti 2 CO 2 , Ti 2 NO 2 , V 2 NO 2 , CrNO 2 , Cr 2 CO 2 , Mo 2 TiC 2 T x, Ti 3 C 2 O 2 , Ti 3 CNO 2 , and Mo 2 CO 2 , are reported as effective supporting materials for monoatomic Pd, Ti, Cu, Mo, Pt, Ni catalysts for CO 2 conversion, CO oxidation, ORR, NRR and HER.…”
Section: Introductionmentioning
confidence: 99%
“…But there are still lack of studies on MXenes supporting metal atom as OER catalysts, except that Cheng et al. predicted Ni anchored on Cr 2 CO 2 as active SAC for both OER and HER …”
Section: Introductionmentioning
confidence: 99%
“…Developing effective bifunctional electrocatalysts for water splitting is one of the central issues in the area of renewable energy. Zhang's team reported a bifunctional electrocatalyst prepared by anchoring the transition metal atoms on the surface of Cr 2 CO 2 MXene for water splitting (Figure b) . The results show that Ni atoms anchored on Cr 2 CO 2 (Ni/Cr 2 CO 2 ) MXene has a low overpotential of 0.16 and 0.46 V for HER and OER, respectively.…”
Section: Electrochemical Energy Conversion and Storage Applicationsmentioning
confidence: 99%
“…Other non-noble metal SAs such as Ni and Cu with mass loading of 0.29 wt% and 3.92 wt%, respectively, were also introduced into Mo 2 C. Other MXenes, such as CrCO 2 were also predicted as potential supports. [66] Novel synthetic strategies are further needed to incorporate single atoms into these supports.…”
Section: Mxenesmentioning
confidence: 99%
“…Cheng et al predicted that Cr 2 CO 2 , another kind of MXene, was a promising support for SACs. [ 66 ] Their calculation results showed that Ni anchored on Cr 2 CO 2 could be quite stable and active in the catalysis of both HER and OER. Besides, in recent years, 2D transition‐metal borides (MBenes), which has similar structure with MXenes, has attracted lots of attention.…”
Section: Catalytic Performance Of Sacs In Hermentioning
confidence: 99%